2019
DOI: 10.3390/nu11030640
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with Hydroxytyrosol and Punicalagin Improves Early Atherosclerosis Markers Involved in the Asymptomatic Phase of Atherosclerosis in the Adult Population: A Randomized, Placebo-Controlled, Crossover Trial

Abstract: Hydroxytyrosol (HT) and Punicalagin (PC) exert cardioprotective and anti-atherosclerotic effects. This study evaluates the effect of oral supplementation with HT and PC (SAx) on early atherosclerosis markers in middle-aged, seemingly healthy adults. A randomized, double-blinded, placebo-controlled, crossover trial was performed for 20 weeks. There were two treatment sequences (Placebo/SAx, n = 41; SAx/Placebo, n = 43) for which the intervention periods (Placebo and SAx) were 8 weeks long, followed by a 4-week … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 73 publications
2
30
0
Order By: Relevance
“…Betanin as a putative activator of the anti-oxidative Nrf2-ARE pathway and supressor of the antiinflammatory NFk-B pathway in CVD As mentioned previously, oxidative stress, inflammation and endothelial dysfunction are common conditions in the pathophysiology of several cardiovascular outcomes, such as atherosclerosis (Quir os-Fern andez et al 2019;F€ orstermann, Xia and Li, 2019), heart failure (Ramirez-Sanchez et al 2013;Koning et al 2016;Lubrano and Balzan 2020), myocardial hypertrophy (Wu et al 2012, Wilder et al 2015) and ischemia and reperfusion injury (Tian et al 2015;Granger and Kvietys 2015).…”
Section: Betanin Atherogenesis and Cardiovascular Diseasesmentioning
confidence: 93%
“…Betanin as a putative activator of the anti-oxidative Nrf2-ARE pathway and supressor of the antiinflammatory NFk-B pathway in CVD As mentioned previously, oxidative stress, inflammation and endothelial dysfunction are common conditions in the pathophysiology of several cardiovascular outcomes, such as atherosclerosis (Quir os-Fern andez et al 2019;F€ orstermann, Xia and Li, 2019), heart failure (Ramirez-Sanchez et al 2013;Koning et al 2016;Lubrano and Balzan 2020), myocardial hypertrophy (Wu et al 2012, Wilder et al 2015) and ischemia and reperfusion injury (Tian et al 2015;Granger and Kvietys 2015).…”
Section: Betanin Atherogenesis and Cardiovascular Diseasesmentioning
confidence: 93%
“…A recent study evaluated the effects of oral supplementation with hydroxityrosol on early atherosclerosis markers in middle-aged healthy adults [143]. Hydroxityrosol showed anti-atherosclerotic properties by improving endothelial function, BP and circulating oxidized LDL levels [144].…”
Section: Olive Oil Polyphenols and Cardiometabolic Diseasesmentioning
confidence: 99%
“…As previously mentioned, a recent study showed that oral supplementation with hydroxityrosol in middle-aged healthy adults exerted anti-atherosclerotic effects by improving endothelial function [144]. In particular, hydroxityrosol may exert its vasculoprotective effects via the activation of a nuclear factor-E (2)-related factor-2 (Nrf2) pathway that increases the expression of other antioxidants, like NAD(P)H: quinone oxidoreductase 1 [193,194].…”
Section: Olive Oil Polyphenols and Cardiometabolic Diseasesmentioning
confidence: 99%
“…Moreover, the increased prevalence of CVD poses considerable burdens for healthcare systems due to the high costs involved in treating and managing the condition [1,2]. Atherosclerosis remains the primary cause of deadly heart diseases [3] and occurs when long-lasting inflammation affects the vascular system.…”
Section: Introductionmentioning
confidence: 99%
“…Punicalagin is a phytochemical polyphenolic compound extracted from pomegranate (Punica granatum) and is the most abundant polyphenol in pomegranate juice (80% w/w) [10]. Punicalagin is known to have strong antioxidant characteristics in comparison to other nutraceuticals [3,11]. Studies on patients undergoing hemodialysis demonstrated that pomegranate juice did not affect or alter inflammatory markers expression after six months of about 1000 mg per day uptake [12].…”
Section: Introductionmentioning
confidence: 99%